Prognostic differences between pre-existing atrial fibrillation in chronic kidney disease and new-onset atrial fibrillation at hemodialysis initiation: a retrospective single-center cohort study - Tomohisa Tsuyuki; Mineaki Kitamura; Haruka Fukuda; Takuma Ishii; Kenta Torigoe; Hiroshi Yamashita; Takahiro Takazono; Noriho Sakamoto; Hiroshi Mukae; Tomoya Nishino (PLoS ONE, 2025)
Atrial fibrillation (AF) can develop in patients with chronic kidney disease. However, the impact of new-onset AF in patients who are initiated on hemodialysis remains unclear. We categorized 254 patients who were started on hemodialysis into three groups: those with pre-existing AF, those with new-onset AF, and those without AF. Statistical analyses were performed to evaluate the associations between patient characteristics and survival outcomes. AF was observed in 42 patients (16.5%), of whom 19 (7.5%) had pre-existing AF and 23 (9.1%) developed new-onset AF at the initiation of hemodialysis. Multivariate logistic regression models showed that only low serum albumin levels were associated with AF (P = 0.04). Age- and other factors-adjusted multivariable Cox regression models indicated that AF, particularly pre-existing AF, was an independent risk factor for death after dialysis initiation (hazard ratio [HR]: 2.28, 95% confidence interval [CI]: 1.39–3.74, P = 0.001; HR: 3.05, 95% CI: 1.64–5.66, P = 0.004, respectively). However, new-onset AF was not significantly associated with mortality (HR: 1.43, 95% CI: 0.74–2.78, P = 0.28). These findings suggest that pre-existing AF before hemodialysis initiation has a crucial impact on patient prognosis.